Mapping of the plant SnRK1 kinase signalling network reveals a key regulatory role for the class II T6P synthase-like proteins - Van Leene, Jelle; Eeckhout, Dominique; Gadeyne, Astrid; Matthijs, Caroline; Han, Chao; De Winne, Nancy; Persiau, Geert; Van De Slijke, Eveline; Persyn, Freya; Mertens, Toon; Smagghe, Wouter; Crepin, Nathalie; et al. (Nature plants, 2022)
The central metabolic regulator SnRK1 controls plant growth and survival upon activation by energy depletion, but detailed molecular insight into its regulation and downstream targets is limited. Here we used phosphoproteomics to infer the sucrose-dependent processes targeted upon starvation by kinases as SnRK1, corroborating the relation of SnRK1 with metabolic enzymes and transcriptional regulators, while also pointing to SnRK1 control of intracellular trafficking. Next, we integrated affinity purification, proximity labelling and crosslinking mass spectrometry to map the protein interaction landscape, composition and structure of the SnRK1 heterotrimer, providing insight in its plant-specific regulation. At the intersection of this multi-dimensional interactome, we discovered a strong association of SnRK1 with class II T6P synthase (TPS)-like proteins. Biochemical and cellular assays show that TPS-like proteins function as negative regulators of SnRK1. Next to stable interactions with the TPS-like proteins, similar intricate connections were found with known regulators, suggesting that plants utilize an extended kinase complex to fine-tune SnRK1 activity for optimal responses to metabolic stress.
Keywords: trehalosa; rostliny; Protein Serine-Threonine Kinases; signální transdukce; protein-serin-threoninkinasy; Signal Transduction; Arabidopsis Proteins; Gene Expression Regulation, Plant; Sugar Phosphates; regulace genové exprese u rostlin; Plants; cukerné fosfáty; Trehalose; proteiny huseníčku